All Days 2002
DOI: 10.2118/79024-ms
|View full text |Cite
|
Sign up to set email alerts
|

Insight from MRI and Micro-Model Studies of Transport of Solvent into Heavy Oil During Vapex

Abstract: Mass transport of solvent into heavy oil during Vapex was studied using techniques of Magnetic Resonance Imaging (MRI) and visual glass micro-models aided by advanced image analyses. Whereas experiments involving MRI images of sand-pack provided detailed description of vapour chamber propagation and phenomena such as asphaltene deposition, diffusion and dilution of heavy oil occurring in the transition zone (on scale of several centimetres), micro-models revealed phenomena at pore level. These included episodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The simulation results of the three cases, using GEM (11) , were compared, on the basis of equivalent production period (10 years) and equivalent solvent injection rates, using monthly production profiles, cumulative production profiles, and GOR profiles. The aim of this study was to investigate the impact of soaking time on solvent recovery performance.…”
Section: Comparison Of Three Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation results of the three cases, using GEM (11) , were compared, on the basis of equivalent production period (10 years) and equivalent solvent injection rates, using monthly production profiles, cumulative production profiles, and GOR profiles. The aim of this study was to investigate the impact of soaking time on solvent recovery performance.…”
Section: Comparison Of Three Casesmentioning
confidence: 99%
“…Because conventional solvent injection is a slow process, which involves molecular diffusion (10) and convective dispersion (11) within the porous medium, we propose that solvent soaking be applied, as an alternative, to promote more effective dilution. Through compositional simulations the optimal soaking time could be obtained based on the selected injection rate and the predetermined solvent mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The diluted and de-asphalted oil, in turn, drains near the edge of the vapour chamber as continuous oil column or, within the transition region as discontinuous oil ganglia 10 . These can be clearly seen in successive MRI images for Athabasca oil-propane system as shown in Figures 6 and 8 after 5 days of elapsed time, as was briefly mentioned earlier.…”
Section: Controlling Asphaltene Deposition During Vapexmentioning
confidence: 99%
“…The precipitated asphaltenes may deposit onto the rock surfaces and cause reservoir plugging in a low-permeability porous medium. In addition, it was reported that the presence of the connate water inside the porous medium results in a faster spreading of the solvent vapour chamber 13,14,15 , an increased initial heavy oil production rate 15 , and a decreased amount of deposited asphaltenes onto the porous media 16 . It was also found that in the presence of the connate water, the precipitated asphaltenes may be carried away from the porous medium by the solvent-diluted heavy oil during its gravity drainage process 16,17 .…”
Section: Introductionmentioning
confidence: 99%